Financial Constraints, Debt Capacity, and the Cross Section of Stock Returns in Nepalese Listed Non-Financial Firms - Bhandari, Nabraj (The Lumbini Journal of Business and Economics, 2021)
This study aims to determine whether debt capacity holds differential impact in the cross section of stock return for financial constrained and financial unconstrained Nepalese enterprises. Considering listed non-financial firm as population, study collect quantitative nature of 10 year balanced panel data from 11 nonfinancial firms listed in Nepal Stock Exchange (NEPSE) and actively traded during the period of 2008 to 2018. Data were obtained by using secondary source. As per propose of the study firm has been categorized financial constrained and financial unconstrained using the basis of book value of assets. Obtained data were analyzed by using multivariate econometric model. Study found that market value of equity, book to market ratio, and debt capacity are major explanatory variables of stock returns for financially constrained firms. Study further found that debt capacity has positive significant impact on stock returns for financial constrained firms. However, with regard to financial unconstrained firm’s debt capacity impact on stock return is insignificant. Study concluded that debt capacity hold differential impact in the cross section of stock returns in Nepalese nonfinancial firms.